Cell-laden hydrogel/titanium microhybrids: Site-specific cell delivery to metallic implants for improved integration. (15th March 2016) - Koenig, Geraldine; Ozcelik, Hayriye; Haesler, Lisa; Cihova, Martina; Ciftci, Sait; Dupret-Bories, Agnes; Debry, Christian; Stelzle, Martin; Lavalle, Philippe; Vrana, Nihal Engin
Graphical abstract: Abstract: Porous titanium implants are widely used in dental, orthopaedic and otorhinolaryngology fields to improve implant integration to host tissue. A possible step further to improve the integration with the host is the incorporation of autologous cells in porous titanium structures via cell-laden hydrogels. Fast gelling hydrogels have advantageous properties for in situ applications such as localisation of specific cells and growth factors at a target area without dispersion. The ability to control the cell types in different regions of an implant is important in applications where the target tissue (i) has structural heterogeneity (multiple cell types with a defined spatial configuration with respect to each other); (ii) has physical property gradients essential for its function (such as in the case of osteochondral tissue transition). Due to their near immediate gelation, such gels can also be used for site-specific modification of porous titanium structures, particularly for implants which would face different tissues at different locations. Herein, we describe a step by step design of a model system: the model cell-laden gel-containing porous titanium implants in the form of titanium microbead/hydrogel (maleimide-dextran or maleimide-PVA based) microhybrids. These systems enable the determination of the effect of titanium presence on gel properties and encapsulated cell behaviour as a miniaturized version of full-scale implants, providing a system compatible with conventional analysis methods. We used a fibroblast/vascular endothelial cell co-cultures as our model system and by utilising single microbeads we have quantified the effect of gel microenvironment (degradability, presence of RGD peptides within gel formulation) on cell behaviour and the effect of the titanium presence on cell behaviour and gel formation. Titanium presence slightly changed gel properties without hindering gel formation or affecting cell viability. Cells showed a preference to move towards the titanium beads and fibroblast proliferation was significantly higher in hybrids compared to gel only controls. The MMP (Matrix Metalloproteinase)-sensitive hydrogels induced sprouting by cells in co-culture configuration which was quantified by fluorescence microscopy, confocal microscopy and qRT-PCR (Quantitative Reverse transcription polymerase chain reaction). When the microhybrid up-scaled to 3D thick structures, cellular localisation in specific areas of the 3D titanium structures was achieved, without decreasing overall cell proliferation compared to titanium only scaffolds. Microhybrids of titanium and hydrogels are useful models for deciding the necessary modifications of metallic implants and they can be used as a modelling system for the study of tissue/titanium implant interactions. Statement of Significance: This article demonstrates a method to apply cell-laden hydrogels to porous titanium implants and a model of titanium/hydrogel interaction at micro-level using titanium microbeads. The feasibility of site-specific modification of titanium implants with cell-laden microgels has been demonstrated. Use of titanium microbeads in combination with hydrogels with conventional analysis techniques as described in the article can facilitate the characterisation of surface modification of titanium in a relevant model system.